Long-acting reversible contraception (LARC) with the intrauterine system with levonorgestrel (6 mcg/d): observational study on the acceptability, quality of life, and sexuality in Italian women. (3rd June 2018) - Neri, Manuela; Piras, Bruno; Paoletti, Anna Maria; Vallerino, Valerio; Corda, Valentina; Ronchetti, Camilla; Taccori, Valeria; Pilloni, Monica; Zedda, Pierina; Capobianco, Giampiero; Dessole, Salvatore; Melis, Gian Benedetto; et al.
Abstract: This observational study was conducted in healthy premenopausal women, who presented themselves for contraception with an intrauterine system (IUS) releasing LNG (6 mcg/d) (Jaydess®, Bayer, Germany) at the outpatient Family Planning Clinics of the Departments of Obstetrics and Gynaecology of the Universities of Cagliari and Sassari (CA/SS), University-Hospitals of CA/SS (Italy). After a screening visit, 31 women without contraindications to Jaydess® were included in the study. No difficulty in Jaydess® insertion (Ji) was found in 87% of subjects, with pelvic pain (PP) (visual analogic scale, VAS:5.33 ± 2.54) reported by 27/31 subjects at the Ji. Pelvic pain was reported by 17/31 subjects on the first day (VAS: 3.07 ± 3.1), 16/31 subjects on the second day (VAS:2.37 ± 2.71), and 11/31 subjects on the third day (VAS:1.18 ± 2.02) from Ji, with a significant ( p  < .001) decrease in the intensity. The primary purposes of the study were to evaluate whether a 12-month-treatment (12-M-T) with Jaydess® interferes on either the quality of life (QoL) or sexuality. Jaydess® did not modify either QoL or sexuality in the 25 subjects who completed the 12-M-T. Throughout the 12-M-T, PP, or pregnancies were not found; the menstrual blood loss was significantly ( p  < .0001) reduced, and the intensity VAS of dysmenorrhea (#14 subjects) significantly ( p  < .001) improved.